Tonta - Hernandez, Jaime (Fantagraphics Books, 2019)
"Though a self-styled loner, Tonta is forced to confront her dysfunctional family history after a weekend of punk rock, lucha libre, and hanging out by the pool with her self-absorbed half sister, Vivian, is disrupted by a botched burglary that leads to the discovery of long-suppressed family secrets"--Provided by publisher.